TLR2, but not TLR4, is required for effective host defence against Chlamydia respiratory tract infection in early life. - Emma L Beckett (PLoS ONE, 2012)
Chlamydia pneumoniae commonly causes respiratory tract infections in children, and epidemiological investigations strongly link infection to the pathogenesis of asthma. The immune system in early life is immature and may not respond appropriately to pathogens. Toll-like receptor (TLR)2 and 4 are regarded as the primary pattern recognition receptors that sense bacteria, however their contribution to innate and adaptive immunity in early life remains poorly defined. We investigated the role of TLR2 and 4 in the induction of immune responses to Chlamydia muridarum respiratory infection, in neonatal wild-type (Wt) or TLR2-deficient ((-/-)), 4(-/-) or 2/4(-/-) BALB/c mice. Wt mice had moderate disease and infection. TLR2(-/-) mice had more severe disease and more intense and prolonged infection compared to other groups. TLR4(-/-) mice were asymptomatic. TLR2/4(-/-) mice had severe early disease and persistent infection, which resolved thereafter consistent with the absence of symptoms in TLR4(-/-) mice. Wt mice mounted robust innate and adaptive responses with an influx of natural killer (NK) cells, neutrophils, myeloid (mDCs) and plasmacytoid (pDCs) dendritic cells, and activated CD4(+) and CD8(+) T-cells into the lungs. Wt mice also had effective production of interferon (IFN)γ in the lymph nodes and lung, and proliferation of lymph node T-cells. TLR2(-/-) mice had more intense and persistent innate (particularly neutrophil) and adaptive cell responses and IL-17 expression in the lung, however IFNγ responses and T-cell proliferation were reduced. TLR2/4(-/-) mice had reduced innate and adaptive responses. Most importantly, neutrophil phagocytosis was impaired in the absence of TLR2. Thus, TLR2 expression, particularly on neutrophils, is required for effective control of Chlamydia respiratory infection in early life. Loss of control of infection leads to enhanced but ineffective TLR4-mediated inflammatory responses that prolong disease symptoms. This indicates that TLR2 agonists may be beneficial in the treatment of early life Chlamydia infections and associated diseases.